The Appeal of Islamic Content in the Digital Era in Shaping the Hearts and Minds of Its Audiences - Miftahul Khoir; M.Toriq al Anshar; Aril Saputra (Penerbit Hellow Pustaka, 2025)
The development of the digital era has created a new ecosystem for the dissemination of Islamic values through various platforms such as YouTube, Instagram, TikTok, and dakwah podcasts. The presence of Islamic content in digital formats not only serves as a medium for conveying religious teachings but also functions as a space for spiritual reflection that can influence the development of character, mindset, and religious behavior within society. This study aims to deeply analyze how the appeal of Islamic content in the digital era can shape the hearts and minds of its viewers. The method used is qualitative through a literature review, examining various sources related to dakwah communication, media psychology, digital religiosity, and Islamic education,The results of the analysis indicate that the appeal of Islamic content is significantly influenced by several key factors. First, the strength of the message, which is able to touch both emotional and rational aspects in a balanced manner, makes the content easier to accept and comprehend. Second, the authenticity and credibility of the content creators, both in terms of knowledge and exemplary behavior, enhance the audience’s trust and psychological closeness. Third, aesthetic elements such as visual design, sound quality, narration, and storytelling help create a deeper and more meaningful viewing experience. Fourth, the relevance of the themes to everyday life challenges—especially those related to morality, religious identity, and modern social dynamics—makes Islamic content more contextual and applicable, This study affirms that Islamic content in the digital era plays an essential role in strengthening Islamic values, enhancing religious awareness, and encouraging positive behavioral changes within society. By employing creative, interactive, and humanistic communication approaches, Islamic content has the potential to become an effective medium for spiritual transformation amid the rapid flow of digital information.